Expression of a lipoxygenase encoding gene (BoLOX1) during postharvest senescence of broccoli - Gómez Lobato, María Eugenia (2012)
Lipoxygenases (LOX) belong to a large family of plant enzymes that catalyze the hydroperoxidation of polyunsaturated fatty acids. Most of them are expressed during senescence and contribute to membrane deterioration and biosynthesis of jasmonic acid, a known senescence enhancer. In this work, we cloned a fragment of a gene encoding a LOX from broccoli (BoLOX1). The analysis of the sequence revealed that BoLOX1 is closely related to other LOX from higher plants. Furthermore, we analyzed the expression of BoLOX1 and detected a larger increase during postharvest senescence. A slight increase of total lipoxygenase activity was also found during senescence. In other sets of experiments, broccoli heads were treated with plant hormones, such as cytokinin and ethylene, as a way to assess the effect of such compounds on the expression of BoLOX1. Cytokinin treatment delayed the increase of BoLOX1 expression and lipoxygenase activity whereas ethylene accelerated both processes. Also, several postharvest treatments were applied in order to delay senescence in broccoli florets and to evaluate their effects on BoLOX1 expression. Samples treated with modified atmosphere, hot air, UV-C or white light showed a delay in chlorophyll degradation and degreening. In most cases, the treatments also delayed the increase of BoLOX1 expression, reaffirming the relationship between the expression of this gene and senescence. However, treatments like modified atmospheres and visible light markedly increased lipoxygenase activity, which suggests a lack of correlation between BoLOX1 expression and lipoxygenase activity.